DISTRIBUTION OF SIEVERS APPLE TREE (Malus sieversii Ledeb. M. Roem) IN THE TERRITORY OF THE ALMATY NATURE RESERVE (Journal of Geography and Environmental Management, 2025)
This article is devoted to the study of the distribution of the Sievers apple (Malus sieversii Ledeb. M. Roem) within the territory of the Almaty State Nature Reserve. The Sievers apple is a relict species of global importance, considered the ancestor of most modern cultivated apple varieties and possessing unique genetic value for breeding and biodiversity conservation. Within the reserve, this species occurs under natural conditions, forming separate stands and groups within the forest belt of the Northern Tien Shan. The aim of the study is to identify the current habitats of Malus sieversii in the reserve, determine its altitudinal distribution, population size, structural composition, and age dynamics. The article examines the ecological conditions affecting the preservation and regeneration of apple forests, including climatic features, soil factors, interspecific interactions, and the degree of anthropogenic impact. The research pays particular attention to the processes of natural regeneration of the Sievers apple and the identification of key threats that limit the expansion of its habitats. The relevance of the study is determined by the urgent need to preserve the gene pool of wild fruit species, among which Malus sieversii occupies a central place as a unique source of resilience and adaptability for cultivated apple forms. The scientific novelty of the work lies in the refinement of data on the current state of Sievers apple populations within the reserve, as well as in the identification of factors that determine their viability and dynamics. The practical significance of the results is expressed in their potential application for the development of measures aimed at preserving apple forests in their natural state and in the creation of a scientific basis for comprehensive monitoring of the biological diversity of the Almaty State Nature Reserve.
Keywords: Sievers apple; Malus sieversii; Almaty State Nature Reserve; distribution; population; biodiversity; conservation